Design proposal of a Maintenance Management System for the Company Pesquera Pacasmayo E.I.R.L. - Cubas Rodríguez, Julio Cesar (2021)
The purpose of this research is to implement preventive maintenance using the tools of: Predictive Maintenance and Total Productive Maintenance (TPM) in the company Pesquera Pacasmayo E.I.R.L.; since, after identifying the constant problems in the production area, it was identified that the main causes of these problems arise from deficiencies in maintenance. The study has a pre-experimental design, in which data collection techniques and instruments were used, specifically in the analysis of information on the company's production and maintenance processes. First, a diagnosis of these areas was carried out to identify the problems that directly affect productivity, in order to determine the maintenance tools to apply; then, the Mean Time Between Failures was found, considering the work data in real time and the number of failures, finding the value of 40 hours for the main machine, 70.94 hours for the hydraulic generator and 54.36 hours for the refrigeration compressor; Average Time Between Repairs, considering the data on the downtime due to breakdown and the number of breakdowns, where the value of 5 hours was found for the main machine, 3.5 hours for the hydraulic generator, and 4 hours for the refrigeration compressor. Regarding availability, 89% was found for the main machine, 95% for hydraulic generators and 93% for refrigeration compressors. Similarly, preventive maintenance was applied to minimize these problems. Total Productive Maintenance (TPM) was also applied, where an increase in productivity is reflected; as well as, an increase of the Total Effectiveness of the team to 15%.